Turning up the heat mimics allosteric signaling in imidazole-glycerol phosphate synthase - Federica Maschietto; Uriel N. Morzan; Florentina Tofoleanu; Aria Gheeraert; Apala Chaudhuri; Gregory W. Kyro; Peter Nekrasov; Bernard Brooks; J. Patrick Loria; Ivan Rivalta; Victor S. Batista (Nature Communications, 2023)
Abstract Allosteric drugs have the potential to revolutionize biomedicine due to their enhanced selectivity and protection against overdosage. However, we need to better understand allosteric mechanisms in order to fully harness their potential in drug discovery. In this study, molecular dynamics simulations and nuclear magnetic resonance spectroscopy are used to investigate how increases in temperature affect allostery in imidazole glycerol phosphate synthase. Results demonstrate that temperature increase triggers a cascade of local amino acid-to-amino acid dynamics that remarkably resembles the allosteric activation that takes place upon effector binding. The differences in the allosteric response elicited by temperature increase as opposed to effector binding are conditional to the alterations of collective motions induced by either mode of activation. This work provides an atomistic picture of temperature-dependent allostery, which could be harnessed to more precisely control enzyme function.